Study of dissolved oxygen quality response in smart watering and autopot systems due to the effect of changes in environmental temperature - Amin, Chaerul; Nur Perwitasari, Sophia Dwiratna; Amaru, Kharistya (Universitas Muhammadiyah Mataram, 2023)
Hydroponics is an agricultural farming system that does not use soil media but uses water media containing nutrient solutions. The purpose of this research is to measure and observe dissolved oxygen levels in the Smart Watering Unpad and Autopot Systems that have never been done before. The research was conducted using descriptive analysis method that is measuring, observing, calculating, and analysing quantitative data on hydroponic installations Smart Watering Unpad and Autopot. The fertigation used in this study were Smart Watering Unpad and Autopot with the parameters observed were ambient temperature, dissolved oxygen, and the relationship between ambient temperature and Dissolved Oxygen for 30 days of observation. The results showed that the response of dissolved oxygen levels was influenced by environmental temperature in the SWU 01 Lettuce, SWU 02, SWU 03, and SWU 01 Paprika systems had a NEGATIVE relationship direction. The Autopot system is the only installation that has a POSITIVE change in the relationship of dissolved oxygen levels influenced by ambient temperature. Autopot is a hydroponic installation that can maintain the availability of dissolved oxygen levels in the nutrient solution. The Smart Watering Unpad 02 installation can maintain the availability of dissolved oxygen levels in the nutrient solution compared to other installations in the Smart Watering Unpad system type.